Histopathological study on the prevalence of trichosporonosis in formalin-fixed and paraffin-embedded tissue autopsy sections by in situ hybridization with peptide nucleic acid probe. (18th September 2019) - Sadamoto, Sota; Shinozaki, Minoru; Nagi, Minoru; Nihonyanagi, Yasuhiro; Ejima, Kozue; Mitsuda, Aki; Wakayama, Megumi; Tochigi, Naobumi; Murakami, Yoshitaka; Hishima, Tsunekazu; Nemoto, Tetsuo; Nakamura, Shigeki; et al.
Abstract: Trichosporon species are some of the most common pathogenic yeasts in Asia, and many are resistant to echinocandin antifungal drugs. Effective treatment of fungal infections requires the selection of appropriate antifungals and the accurate identification of the causal organism. However, in histopathological specimens Trichosporon spp. are often misidentified as Candida species due to morphological similarities. In situ hybridization (ISH) is a useful technique for identifying fungal species in formalin-fixed and paraffin-embedded (FFPE) tissue sections. Although many novel probes for ISH are available, the practical use of ISH for identification of fungi remains limited, in part due to the lack of adequate verifications. We conducted a two-center retrospective observational study in which the ISH technique was used to differentiate Trichosporon spp. and C. albicans in FFPE tissue from autopsy specimens. The study included 88 cases with blood stream yeast infection without Cryptococci extracted from 459 autopsy files of cases with proven invasive fungal infection (IFI). Positive signals for the Trichosporon spp. protein nucleic acid (PNA) probe and C. albicans PNA probe were seen for 7 and 35 cases, respectively, whereas the remaining 46 were negative for both. For the Trichosporon spp.- positive specimens, 5/7 were reported as candidiasis in autopsy records. Our results suggested that accurate histological identification of fungal infections remains challenging, but ISH may be a suitable approach to support histological findings. In addition, this retrospective study suggested that trichosporonosis may have high prevalence among cases of bloodstream yeast infections in Japan.